EFEKTIVITAS STRATEGI PELATIHAN CALON TENAGA KERJA DI BALAI BESAR PELATIHAN VOKASI DAN PRODUKTIVITAS (BBPVP) SERANG - Nursapial, Ila; Hatroko, Gatot; Wajir, Dede Qodrat Al (Gapenas Publisher, 2025)
The purpose of this research is to assess the training strategy implemented by BBPVP Serang to maximize the training of prospective workers so that participants are fully prepared for industrial absorption. Training strategies also play a crucial role in reducing unemployment in Indonesia, particularly in Banten. This study employed qualitative methods, using techniques for data collection including observation, interviews, and documentation studies. This research utilized Sutrisno's (2010) Theory of Effectiveness, which has five indicators for assessing program effectiveness: program understanding, targeting accuracy, timeliness, goal achievement, and tangible change.The results indicate that the training program organized by BBPVP Serang is not fully effective, as evidenced by the suboptimal workforce absorption. The lack of industry involvement in developing the training strategy leads to low workforce absorption. Limited training hours also make the training less than optimal. However, there are also supporting factors that contribute to the strategy's effectiveness in workforce distribution, such as industry involvement, such as instructor involvement, training duration, and an industry-focused curriculum. This research also emphasizes how the strategy can have a more effective impact on training participants so that after the training is held, the participants can be channeled well.